Prerequisites and certain aspects of implementation of an integrated approach to regulating industrial pollution in Ukraine - Aleksyeyeva, Yelyzaveta; Vykhryst, Serhiy; Skrylnikov, Dmytro; Sushko, Svitlana; Вихрист, Сергій Михайлович; Вихрист, Сергій (Environmental Law Network International, 2022)
The piece explores the prerequisites of implementation of an integrated approach to regulating industrial pollution in Ukraine as well as provides an insight into the legislative proposals on introduction of the integrated environmental permits currently under consideration in the Parliament of Ukraine. The article argues that the proposed regulation corresponds to the respective EU acquis, including the Aarhus Convention. Given that the post-war reconstruction assistance has already been clearly anchored in the green and digital transitions as well as other fundamental European values, it is the authors’ conclusion that the new legal framework on reduction, prevention and control of industrial pollution will be introduced in Ukraine in the nearest future